Toward a Physics of Interdependence for Autonomous Human-Machine Systems: The Case of the Uber Fatal Accident, 2018 - Lawless, William (Frontiers in Physics, 2022)
Computational autonomy has recently begun to receive significant attention, but neither the theory nor the science has developed sufficiently to be able to design and operate an autonomous human-machine system (HMS). In this review, and as a theory-in-progress, we review the shift from laboratory studies, which have been unable to advance the science of autonomy, to a theory of autonomy in open and uncertain environments based on autonomous human systems along with supporting evidence in the field. We attribute the need for this shift to the social sciences being primarily focused on the science of individual agents, whether for humans or machines, a focus that has been unable to generalize to new situations, new applications, and new theory. Specifically, the failure of traditional systems predicated on the individual to mimic, replicate, or instantiate what it means to even be the social is at the very heart of the impediment to be conquered and overcome as a prelude to the mathematical physics we explore. As part of this review, we present a case study of how an autonomous human system investigates a self-driving car fatality, how the human-machine team failed to prevent the fatality; and how an autonomous human-machine system might approach the same problem in the future. To advance the science, we reject independence among teammates as a viable scientific approach and instead explore what we know about a theory of interdependence for human-machine systems (HMS). We discuss our review, the theory of interdependence, and we close with a few generalizations and future plans.